Preliminary study on the preparation of antler powder/chitosan/β-glycerophosphate sodium/polyvinyl alcohol porous hydrogel scaffolds and their osteogenic effects - Abudukelimu, Kudelaiti; Aierken, Aikepaer; Tuerxuntayi, Ailifeire; Yilihamu, Yilizhati; Abulizi, Saierdaer; Wufuer, Duolikun; Dong, Hongbin (Frontiers in Bioengineering and Biotechnology, 2024)
The production of bone-like structural scaffolds through bone tissue engineering technology is a promising method for bone regeneration to repair bone defects. Deer antler, an easily harvested and abundantly sourced initial bone tissue structure, resembles the composition and structure of human cancellous bone and can serve as a new material for allogeneic bone transplantation. This study involved the preparation and characterization of antler powder/chitosan/β-glycerophosphate sodium/polyvinyl alcohol (AP/CS/β-GP/PVA) porous hydrogel scaffolds to verify their material properties and osteogenic mechanisms. The microstructure, hydrophilicity, and mechanical properties of the scaffolds were studied using Scanning Electron Microscopy (SEM), contact angle measurement, and a universal material testing machine, respectively. The interactions between the various components were investigated using Fourier-Transform Infrared Spectroscopy (FTIR). On the other hand, the biocompatibility, osteogenic properties, and expression of osteogenesis-related proteins of the scaffolds were evaluated through Cell Counting Kit-8 (CCK-8) assays, alkaline phosphatase staining, Alizarin Red staining, live/dead cell staining, and Western blot analysis. The results showed that as the content of deer antler powder increased, both the hydrophilicity and mechanical properties of the scaffold materials improved, while the porosity slightly decreased with an increase in deer antler powder content. Cell culture experiments demonstrated that scaffolds with a higher proportion of deer antler powder were beneficial for the proliferation and differentiation of mouse pre-osteoblast (MC3T3-E1) cells, with the scaffolds containing 10% and 8% deer antler powder showing the best effects. The upregulation of RUNX2, OCN, OSX, and OPN protein expression may promote differentiation. Therefore, the AP/CS/β-GP/PVA hydrogel scaffolds have the potential to become a promising biomaterial for bone tissue engineering.